The missing conformer: A comprehensive rotational spectroscopy study and astronomical search of two conformers of methyl cyanoacetate - Batra, Gayatri; Pinacho, Pablo; Steber, Amanda L.; Rivilla, Víctor M.; Martín-Pintado, Jesús; Jiménez-Serra, Izaskun; Schnell, Melanie (Frontiers in Astronomy and Space Sciences, 2022)
We performed a comprehensive investigation of methyl cyanoacetate (MCA) using high-resolution Fourier transform rotational spectroscopy. Two low energy conformers of MCA were observed in the vibrational ground state, in selected frequency regions from 2 to 110 GHz. We report accurately determined line lists, rotational constants, centrifugal distortion constants, and nuclear quadrupole coupling constants for both conformers, as well as for several singly substituted heavy-atom isotopologues. One of the conformers was previously reported; however, the rotational transitions of the second conformer, which is newly described here, are observed to be generally more intense than the latter. The accurate predictions of rotational transitions into the millimeter-wave region can facilitate the detection of these conformers of MCA in the interstellar medium. Using the rotational spectroscopy data provided here, we searched for the two conformers of MCA in a deep and unbiased spectral survey of the molecular cloud G+0.693-0.027 located in the Galactic Center. None of the MCA conformers were detected. The upper limits for their abundances were derived with respect to the abundance of molecular hydrogen.